The Influence of Service Quality, Trust and Customer Value on Customer Satisfaction at Gerai Indosat Ooredoo WTC Surabaya - Eko Wahyu Nugroho; Elok Damayanti (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
The purpose of this research is to find out The Influence of Service Quality, Trust and Customer Value on Customers Satisfaction at Gerai Indosat Ooredoo WTC Surabaya in simultaneously and partially. This Research used quantitative method with 70 respondents of population and samples were collected by giving questionnaires to the customers who have bought Samsung’s Bundling Product from Gerai Indosat Ooredoo WTC Surabaya. The data was analyzed used multiple linear regression technique and classic assumption test. The results showed that the hypotheses have effects to Customers’s Satisfaction simultaneously and partially.